2018
DOI: 10.1093/cid/ciy935
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of Concomitant Strongyloides stercoralis Infection in Patients With Type 2 Diabetes Mellitus

Abstract: Background Human and animal studies have demonstrated that helminth infections are associated with a decreased prevalence of type 2 diabetes mellitus (T2DM). However, very little is known about their biochemical and immunological interactions. Methods To assess the relationship between a soil-transmitted helminth, Strongyloides stercoralis (Ss), and T2DM, we examined analytes associated with glycemic control, metabolic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 46 publications
5
88
1
Order By: Relevance
“…The baseline demographic characteristics and biochemical parameters of Ss+ and Ss-individuals are shown in Table 1. As shown and as described previously [13], there were no significant differences in age, sex, BMI or other biochemical parameters between the two groups.…”
Section: Study Population Characteristicssupporting
confidence: 86%
See 3 more Smart Citations
“…The baseline demographic characteristics and biochemical parameters of Ss+ and Ss-individuals are shown in Table 1. As shown and as described previously [13], there were no significant differences in age, sex, BMI or other biochemical parameters between the two groups.…”
Section: Study Population Characteristicssupporting
confidence: 86%
“…All the study participants were assessed as part of a natural history study protocol (12-I-073) approved by Institutional Review Boards of the National Institute of Allergy and Infectious Diseases (USA) and the National Institute for Research in Tuberculosis (India), and informed written consent was obtained from all participants. This was the same study population that was previously used for assessment of metabolic parameters [13].…”
Section: Ethics Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, they could show a significant deterioration of these parameters after anthelmintic therapies. 58 Two others studies in Indonesia and Uganda demonstrated similar outcomes after treatment against STHs and S. mansoni, respectively. 59,60 Finally, a cross-sectional analyses of several studies linking helminth infection and metabolic syndrome confirmed the trend towards a decreased prevalence of metabolic syndrome in people with past or present helminth infection.…”
Section: A Negative Association Between Helminth Infection and Metabomentioning
confidence: 86%